Keterampilan Dasar Guru Profesional Terhadap Kualitas Proses Pembelajaran - Bagus Cahyadi; Muhammad Fahri; Jafar Sidiq; Rydan Alpin Putra; Muhammad Arwanda Lutfi; Wagiman Manik (Tasqif: Journal of Islamic Pedagogy, 2026)
Basic teaching skills are one of the essential factors that determine the quality of the learning process in the classroom. Teachers are not only required to master subject matter but also to possess teaching skills that support effective, interactive, and meaningful learning. This study aims to examine the concept of skills, the forms of basic teaching skills, and the impact of teachers’ basic skills on the learning process of students. This research employs a qualitative descriptive approach using a library research method by analyzing relevant literature from both general education and Islamic education perspectives. The findings indicate that basic teaching skills include skills in opening and closing lessons, explaining material, questioning, using instructional media, providing reinforcement, varying teaching strategies, guiding discussions, and managing the classroom. Mastery of these skills has a positive impact on the quality of the learning process, as reflected in improved students’ understanding, learning motivation, active participation, and the creation of a conducive learning environment. From the perspective of Islamic education, teachers’ basic skills also represent professionalism, responsibility, and the principle of itqān in fulfilling the educational mandate. Therefore, strengthening basic teaching skills is a fundamental requirement for improving the quality of the learning process in a sustainable manner. Keterampilan dasar guru memiliki peran penting dalam menentukan kualitas proses pembelajaran. Guru tidak hanya dituntut menguasai materi, tetapi juga memiliki keterampilan mengajar yang mendukung terciptanya pembelajaran yang efektif dan bermakna. Penelitian ini bertujuan untuk mengkaji pengertian keterampilan, bentuk keterampilan dasar mengajar, serta dampaknya terhadap proses pembelajaran siswa. Penelitian ini menggunakan pendekatan kualitatif deskriptif melalui studi kepustakaan dengan menelaah berbagai sumber literatur pendidikan dan pendidikan Islam. Hasil kajian menunjukkan bahwa keterampilan dasar guru meliputi keterampilan membuka dan menutup pembelajaran, menjelaskan, bertanya, menggunakan media, memberikan penguatan, variasi mengajar, membimbing diskusi, dan mengelola kelas. Penguasaan keterampilan tersebut berdampak positif terhadap peningkatan pemahaman, motivasi, keaktifan siswa, serta terciptanya proses pembelajaran yang efektif dan kondusif. Dalam perspektif pendidikan Islam, keterampilan dasar guru mencerminkan profesionalisme dan tanggung jawab dalam menjalankan amanah sebagai pendidik.